Fruits of Knowledge: Polemics, Humour and Moral Education in the Writings of Rokeya Sakhawat Hossain, Lila Majumdar and Nabaneeta Dev Sen - Bagchi, Utrecht University, Netherlands, Barnita (Asiatic: IIUM Journal of English Language and Literature, 2013)
This paper analyses literary sources, by three women writing in Bengali, from c.1900 to Â contemporary times. These writings offer far more complex, heterogeneous, innovative and creative strategies for the shaping, reform and moral education of subjects, than have hitherto been recognised. Authors focused on in the article are Rokeya Sakhawat Hossain (1880-1932), Lila Majumdar (1908-2007) and Nabaneeta Dev Sen (1938-). â€œMoral educationâ€ and â€œreformâ€ have tended to carry with them a stereotypical aura of sententiousness, didacticism, humourlessness and aridness. I argue, utilising tools from literary and gender studies, that polemical and fictional writing by Bengali women writers such as Rokeya, Lila and Nabaneeta repay attention to their stylistic fertility, their ability to craft and reinvent humour and their creative reinvention of genres. The projects of reform and moral education of subjects (not only female ones) that emerge from such writing are nuanced, multilayered, subversive and wickedly intelligent.Â 